2006
DOI: 10.1038/sj.bjc.6603501
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the long-term impact of a prophylactic human papillomavirus 16/18 vaccine on the burden of cervical cancer in the UK

Abstract: To predict the public health impact on cervical disease by introducing human papillomavirus (HPV) vaccination in the United Kingdom, we developed a mathematical model that can be used to reflect the impact of vaccination in different countries with existing screening programmes. Its use is discussed in the context of the United Kingdom. The model was calibrated with published data. The impact of vaccination on cervical cancer and deaths, precancerous lesions and screening outcomes were estimated for a vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 36 publications
6
74
1
6
Order By: Relevance
“…Our results differ from other studies that have shown more favorable effects (Goldie et al 2004;Barnabas and Garnett 2005;Elbasha et al 2007;French et al 2007;Insinga et al 2007;Kohli et al 2007;Dasbach et al 2008). This is firstly due to the different research question in our study, which addresses population-wide benefits for a given time period rather than health effects for vaccinated cohorts.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our results differ from other studies that have shown more favorable effects (Goldie et al 2004;Barnabas and Garnett 2005;Elbasha et al 2007;French et al 2007;Insinga et al 2007;Kohli et al 2007;Dasbach et al 2008). This is firstly due to the different research question in our study, which addresses population-wide benefits for a given time period rather than health effects for vaccinated cohorts.…”
Section: Discussioncontrasting
confidence: 56%
“…They have been developed for several countries, often in combination with an economic evaluation (Kulasingam and Myers 2003;Sanders and Taira 2003;Goldie et al 2004Goldie et al , 2007Taira et al 2004;Barnabas and Garnett 2005;Garnett et al 2006;Brisson et al 2007;Elbasha et al 2007;French et al 2007;Insinga et al 2007;Kohli et al 2007 Thiry et al 2007;Bergeron et al 2008;Dasbach et al 2008;Jit et al 2008;Kim and Goldie 2008;Kulasingam et al 2008). However, for producing reliable results, countryspecific models are required that take into account countryspecific features such as screening policy, epidemiology of the disease under evaluation and HPV prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…The high risk HPV types 16 and 18, contribute to about 70% of cervical cancer cases (Smith et al, 2008;Seoud, 2011). Clinical trial studies have demonstrated that two vaccines (Gardasil ® and Cervarix ® ) have almost 100% efficacy in preventing persistent infection and the development of precancerous lesions caused by HPV16 and HPV18 (Kohli et al, 2007;Paavonen et al, 2009;Lehtinen et al, 2012;Schiffman and Wacholder, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Questi modelli dimostrano come la vaccinazione anti HPV, in aggiunta ai programmi di screening, comporta tanto una riduzione significativa del rischio di contrarre il cervicocarcinoma, quanto una riduzione dei risultati anormali del pap test [6,7].…”
Section: Il Modello Per L'impatto Della Vaccinazione Anti Hpvunclassified